Tobacco consumption and gender socioeconomic differences in south Europe : Evidence from panel data - Nikolaou, Angeliki (SPOUDAI Journal of Economics and Business, 2009)
The purpose of this paper is to investigate the socioeconomic inequalities of individual smoking behaviour across four south EU countries. Three indicators for the socioeconomic status of the individuals are used; equivalised household income, educational level and employment status. According to our findings Italy is the only country where socioeconomic inequalities in smoking behaviour are quite clear for both genders. For the rest three countries weak socioeconomic inequalities or even reverse educational gradient for the female population is observed. Socioeconomic inequalities in smoking behaviour are emerging in this part of the EU region. Incorporating inequality aspects into antismoking measures will assist a more targeted tobacco control policy. JEL Classifications: I12, I18, C23.